1998
DOI: 10.1590/s0100-879x1998000400008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal nocturnal blood pressure fall in normotensive adolescents with insulin-dependent diabetes is ameliorated following glycemic improvement

Abstract: Lack of the physiological nocturnal fall in blood pressure (BP) has been found in diabetics and it seems to be related to the presence of diabetic complications. The present study examined the changes in the nocturnal BP pattern of 8 normotensive insulin-dependent diabetic adolescents without nephropathy following improvement in glycemic control induced by an 8-day program of adequate diet and exercise. The same number of age-and sex-matched control subjects were studied. During the first and eighth nights of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
2
5
1
2
Order By: Relevance
“…Additionally, insulin plays an important role in regulating the autonomous nervous system. Improvement in glycemic control for one week in Type 1 DM decreased the ABPM pressure means and increased the BP fall during the night 49 , reinforcing the theory exposed.…”
Section: Masked Hypertension (%)supporting
confidence: 68%
“…Additionally, insulin plays an important role in regulating the autonomous nervous system. Improvement in glycemic control for one week in Type 1 DM decreased the ABPM pressure means and increased the BP fall during the night 49 , reinforcing the theory exposed.…”
Section: Masked Hypertension (%)supporting
confidence: 68%
“…These findings are consistent with the hypothesis that poor metabolic control is a major determinant of nervous damage. Indeed, other studies of type 1 diabetic patients have shown that autonomic nervous system abnormalities could be reversed when better metabolic control was obtained (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…We investigated cardiovascular and autonomic function, in rats weighing 166 ± 4 g,[5][6][7]14,30, 45, and 90 days after STZ injection (N = 24,33,27,14,and 13, respectively). Arterial pressure (AP), mean AP (MAP) variability (standard deviation of the mean of MAP, SDMMAP), heart rate (HR), HR variability (standard deviation of the normal pulse intervals, SDNN), and root mean square of successive difference of pulse intervals (RMSSD) were measured.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insulin has a role in regulating the autonomic nervous system [152]. Ferreira et al [153] demonstrated that an improved glycemic control in patients with type 1 DM was associated with decreased ABPM pressure averages and increased blood pressure fall overnight.…”
Section: Role Of Diabetic Autonomic Neuropathy and Absence Or Reductimentioning
confidence: 99%